Hubungan Antara Paritas Dan Umur Ibu Dengan Anemia Pada Ibu Hamil Trimester III di BPM Erlina Herawati Tahun 2023 - Nurmalina Hutahaean; Asmawaty Asmawaty (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
The increase in the incidence of anemia in Medan City from 2020 to 2023, peaking at 32.39%, is the focus of research. This study aims to assess the relationship between parity and maternal age and anemia in third trimester pregnant women at BPM Erlina Herawati, Medan City in 2023. The chi-square test was used for data analysis. The results showed that there was no significant relationship between maternal age and anemia in pregnant women in the third trimester at BPM Erlina Herawati in 2023 (p-value 0.243). However, there was a significant relationship between parity and anemia in this group (p-value 0.023, RP 0.328). The research conclusion states that there is no significant relationship between maternal age and anemia, but there is a significant relationship between parity and anemia in pregnant women in the third trimester at BPM Erlina Herawati in 2023. This study provides new insights regarding the risk factors for anemia in this population.